Kinetics and mechanism of sphalerite leaching by sodium nitrate in sulphuric acid solution - Sokić M.; Marković B.; Matković V.; Živković D.; Štrbac N.; Stojanović J. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Interest for application of hydrometallurgical processes in a processing of complex sulphide ores and concentrates has increased in recent years. Their application provides better metal recoveries and reduced emission of gaseous and toxic ageneses in the environment. The kinetics and mechanism of sphalerite leaching from complex sulphide concentrate with sulphuric acid and sodium nitrate solution at standard conditions was presented in this paper. The influences of temperature and time on the leaching degree of zinc were investigated and kinetic analysis of the process was accomplished. With temperature increasing from 60 to 90°C, the zinc leaching increased from 25.23% to 71.66% after 2 hours, i.e. from 59.40% to 99.83% after 4 hours. The selected kinetic model indicated that the diffusion through the product layer was the rate-controlling step during the sphalerite leaching. The activation energy was determined to be 55 kJ/mol in the temperature range 60-90°C. XRD, light microscopy and SEM/EDX analyses of the complex concentrate and leach residue confirmed formation of elemental sulphur and diffusion-controlled leaching mechanism.